The Contribution Of Sharia Economy In Creating Indonesia's Economic Stability During The Covid-19 Pandemic - Alissa Qothrun Nada; Wardatus Saniyyah (JOSSE: Journal of Social Science and Economics, 2023)
From 2020 to 2021, Indonesia experienced an economic downturn due to the COVID-19 pandemic. Not only Indonesia, the whole world also experienced a similar impact. Various Efforts Government measures and the role of Islamic Financial Institutions are important in creating economic stability. This study aims to examine the contribution of the Islamic economy in creating economic stability in Indonesia during the Covid-19 pandemic. The approach in this study is to use a qualitative approach. The data was collected by examining the source of squandered data in the form of research publications and official government news. Data analysis uses Huberman's miles theory in the form of data reduction, data presentation, and conclusions. The results showed that the Islamic economy greatly contributed to creating economic stability during the Covid-19 pandemic. Some indications include the strengthening of social philanthropy funds both from Islamic financial institutions and from LAZ. In addition, the contribution of the Islamic economy is also realized by programs disbursed to MSMEs by Islamic banks in Indonesia. The results of this study corroborate other research that Islamic economics has a significant role in economic development in the world, including in Indonesia